2021
DOI: 10.1186/s12889-021-12280-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise interventions on mental health and health-related quality of life in women with polycystic ovary syndrome: a systematic review

Abstract: Background Polycystic ovary syndrome (PCOS) is a complex condition, impacting cardio-metabolic and reproductive health, mental health and health-related quality of life. The physical health benefits of exercise for women with PCOS are well-established and exercise is increasingly being recognised as efficacious for improving psychological wellbeing. The aim of this review was to summarise the evidence regarding the effectiveness of exercise interventions on mental health outcomes in women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Although exercise is an effective means for managing mental health concerns in a general population 50 , this relationship has been relatively understudied in women with PCOS. Existing research reports a combination of positive and null findings, with approximately half of existing studies reporting significant improvements in symptoms of anxiety and/or depression 23 , 24 . To the best of our knowledge, this is the first study to compare work-matched HIIT and MICT exercise interventions on mental health and HRQoL in women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although exercise is an effective means for managing mental health concerns in a general population 50 , this relationship has been relatively understudied in women with PCOS. Existing research reports a combination of positive and null findings, with approximately half of existing studies reporting significant improvements in symptoms of anxiety and/or depression 23 , 24 . To the best of our knowledge, this is the first study to compare work-matched HIIT and MICT exercise interventions on mental health and HRQoL in women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the Australian physical activity guidelines, the International evidence-based guidelines for the assessment and management of PCOS recommend a minimum of 150 min per week of moderate intensity physical activity or 75 min per week or vigorous intensity exercise 19 . Exercise is well established as a therapeutic tool to improve metabolic and reproductive health outcomes in women with PCOS 21 , 22 , however, the impact on mental health and HRQoL is less clear 23 , 24 . In populations with other chronic conditions, exercise is known to be an effective tool for promoting positive mental health 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that, regardless of modality, any exercise program with a duration of 45–60 min per session and at least moderate intensity significantly improved cognitive function. In a systematic review involving 11 randomized, non-randomized, and uncontrolled trials, Pattern et al [ 38 ] examined the effects of exercise interventions on mental health and health-related quality of life in women with poly ovary syndrome. In that study, they showed that exercise training improved health-related quality of life in all 11 trials, and half of the 11 studies reported significant improvements in depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Mental disorders may increase the severity of pain, whereas prolonged periods of pain contribute to the increased severity of mental disorders involving fear, stress, depression, and anxiety. Numerous HRQoL surveys have characterized mental disorders as a dominant aspect of the lives of patients with PCOS [ 16 , 17 , 18 , 20 , 22 , 23 , 24 , 25 , 26 , 134 ] and a factor that may affect their pain perception. However, the association between pain and mental disorders in patients with PCOS requires further clarification.…”
Section: Summary and Discussionmentioning
confidence: 99%